Strategi Digital Marketing dalam Meningkatkan Daya Saing Pelaku Ekonomi Kreatif : Studi Kasus pada Usaha Kain Tenun Bali Dewi di Singaraja - Dewi, Ni Putu Sthira Sattwika; Suwendra, I Wayan (Jurnal Pendidikan Ekonomi Undiksha, 2025)
This study aims to analyze and formulate the right digital marketing strategy to increase the competitiveness of creative economy actors, especially in the traditional woven cloth business "Bali Dewi" located in Buleleng Regency, Bali. The method used is a descriptive qualitative case study, with data collection techniques through in-depth interviews, field observations, and documentation. Informants in this study consisted of business owners, related government agencies, and consumers. The results of the study show that the "Bali Dewi" business still relies on conventional marketing strategies such as word of mouth and participation in local exhibitions. Although it already has social media, its management is not optimal and is not integrated with digital sales systems such as marketplaces or websites. The inhibiting factors found include low digital literacy, limited human resources and infrastructure, minimal training, and the absence of an official online store. This makes it difficult for businesses to compete with competitors outside the region who have actively used digital marketing strategies.